Housing design for the urban district - Ramos, Grace C. (2005)
Planning by the public sector has often been carried out using a "template approach." This approach takes off from the assumption that all areas being planned for are the same in terms of physical and social qualities. It is, however, important to note that each city is unique in function and features. Urban planning, therefore, should factor in the special characteristics that arise out of the district's role in the city and even national affairs. Districts can be categorized under any of the following: The Central Business District serves as the hub for the service sector of the economy. Closely associated and oftentimes adjacent to CDB's are downtowns that serve as the outlets for the manufacturing sector. Institutional districts are distinguished by the concentration of educational, religious, cultural and government buildings. Industrial districts are production centers where efficiency of operations is of prime importance. Tourism districts are defined by the presence of historically significant natural and man-made assets. Usually located on waterfronts, Market districts cater to wholesale trading. Circulation networks, terminals, parking spaces of organic development and territorial specialization. These are natural processes that arise out of very strong economic and social forces that physical planning must go along with.
Keywords: Housing; Dwellings